Comics and graphic novels - Round, Julia (New York, NY : Bloomsbury Academic, 2023)
"Providing an overview of the dynamic field of comics and graphic novels for students and researchers, this Essential Guide contextualises the major research trends, debates and ideas that have emerged in Comics Studies over the past decades. Interdisciplinary and international in its scope, the critical approaches on offer spread across a wide range of strands, from the formal and the ideological to the historical, literary and cultural. Its concise chapters provide accessible introductions to comics methodologies, comics histories and cultures across the world, high-profile creators and titles, insights from audience and fan studies, and important themes and genres, such as autobiography and superheroes. It also surveys the alternative and small press alongside general reference works and textbooks on comics. Each chapter is complemented by list of key reference works"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Comic books, strips, etc. -- history & criticism; Graphic novels -- history & criticism